Stereotactic Radiofrequency Ablation of Liver Tumors in Octogenarians - Schullian, Peter; Putzer, Daniel; Silva, Michael A.; Laimer, Gregor; Kolbitsch, Christian; Bale, Reto (Frontiers in Oncology, 2019)
Purpose This study aimed to evaluate the efficacy and overall clinical outcome of patients over the age of eighty undergoing stereotactic radiofrequency ablation (SRFA) and to compare the results to a younger population with propensity score matching. Material and methods Between 2006 and 2018 36 patients aged between 80 and 90 years underwent 46 SRFA sessions of 70 primary and secondary liver tumors. For comparison of treatment safety and efficacy 36 younger patients were selected with propensity score matching by the R package “MatchIt” in this retrospective, single-center study. Results 68/70 tumors were successfully ablated at first ablation session (97% primary technical efficacy rate). Local tumor recurrence developed in 5 of 70 nodules (7.1%). The complication rate above Clavien-Dindo Grade III was 6.5% (3 of 46). The overall survival (OS) rates at 1-, 3-, and 5- years from the date of the first SRFA were 84.6%, 50.5%, and 37.9% for HCC patients and 87.5%, 52.5% at 1-, and 3-years for CRC patients. The disease-free survival (DFS) for HCC patients after SRFA was 79.1%, 35.6%, and 23.7%, at 1-, 3- and 5- years, and 75%, 22.5% at 1-, and 3-years for CRC patients. There were no significant differences in terms of technical efficacy, local recurrences, major complications, OS and DFS compared to the control group. Conclusion SRFA in octogenarians is a safe, feasible and useful option in the management of primary or metastatic liver tumors with no significant difference in outcomes compared to a younger control group.